Association of phase angle and appendicular upper and lower body lean soft tissue with physical performance in young elite soccer players: a pilot study - Bongiovanni, T.; Rossi, A.; IAIA, F. M.; Alberti, G.; Pasta, G.; Trecroci, A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: In soccer, a better understanding of the bioimpedance parameters with physical performance may be useful to efficiently monitor and interpret players` performance variation throughout a certain period of the season. Therefore, this study aimed to examine the association between phase angle (PhA) and arms and legs lean soft tissue (ALST and LLST) with physical performance in young elite soccer players. METHODS: Fifteen young male elite soccer players (age: 14.2±1.2 years, BMI=20.51±1.38 kg/m2) participated in this investigation. Raw bioimpedance parameters (reactance, resistance, and PhA) were obtained by a bioelectrical impedance analysis (BIA) device. Then, ALST and LLST were estimated. All players underwent a physical testing battery including countermovement jump (CMJ), 10-minute and 20-minute sprint, and Yo-Yo Intermittent Recovery Test level 1 (YoYo IRTL1) in the domains of anaerobic and aerobic performance, respectively. RESULTS: The results showed that LST (total, arms and legs) positively correlated with CMJ (0.64<r<0.69; P<0.001) and negatively correlated with 10-m (-0.59<r<-0.63; P<0.05) and 20-minute sprint (-0.67<r<-0.73; P<0.001), while PhA positively correlated with CMJ (r=0.57; P<0.05) and negatively correlated (r=-0.54; P<0.05) only with 20-minute sprint. No significant association was found between the BIA-related parameters (PhA and LST) and Yo-Yo IRT level 1. CONCLUSIONS: The present findings highlight the existing association of PhA and LST with jumping and sprinting performance in young elite soccer players. This result supports the use of BIA-related measures as a simple and practical approach to monitoring anaerobic performance changes, rather than aerobic, over time throughout the season.